Dabrafenib plus trametinib rechallenge in four melanoma patients who previously progressed on this combination. Issue 2 (April 2017) - Rogiers, Aljosja; Wolter, Pascal; Bechter, Oliver
Abstract : In unresectable or metastatic melanoma with a BRAF V600 mutation, combined BRAF/MEK targeted therapy improves clinical outcomes. Yet, disease progression because of acquired resistance occurs in the majority of patients. There is emerging evidence that resistance to BRAF-inhibitor-based targeted therapy can be reversible in some cases. We retrospectively analyzed four patients with BRAF -mutant stage IV cutaneous melanoma who were treated with dabrafenib plus trametinib and rechallenged with the same combination after previously experiencing progression. At initial treatment with dabrafenib plus trametinib, three patients achieved a partial response and one patient achieved a complete response. Progression-free survival varied from 9.9 to 24.3 (median 19.8) months. The targeted therapy-free interval ranged from 2.3 to 11.7 (median 8.8) months. At rechallenge, all four patients had a partial response, with progression-free survival ranging from 3.6 to 6.8 (median 5.2) months. Clinical benefit and a second radiological response can be obtained upon readministration of dabrafenib plus trametinib after previously acquiring resistance to this combination. A better understanding of the biological underpinnings of genomic and nongenomic mechanisms of resistance to BRAF-inhibitor-based targeted therapy is needed to identify patients who may benefit from this rechallenge approach.